Rigid Neuroendoscopy Assisted Hematoma Resection Reduces the Recurrence Rate of Chronic Subdural Hematoma With Mixed Density: A Retrospective Analytic Cohort Study - Fang, Huangyi; Zhang, Zhongding; Liu, Yiru; Wang, Lingfei; Yang, Yue; Li, Shize; Jing, Xiepan; Bai, Guanghui; Sheng, Hansong (Frontiers in Surgery, 2022)
Background: The mixed density hematoma (MDH) has a high recurrence rate in chronic subdural hematoma (CSDH). This study adopted rigid neuroendoscopy assisted hematoma resection to evacuate CSDH and investigated its efficacy as compared with the traditional burr-hole craniostomy (BHC) in CSDH with mixed density. Methods: A retrospective cohort study was conducted at two centers between January 2015 and December 2020. The data of 124 patients who underwent BHC for CSDH with mixed density were collected and analyzed. A total of 41 patients underwent rigid neuroendoscopy assisted hematoma resection (neuroendoscopy group) and 83 patients were treated by the traditional BHC (control group). Follow-ups were conducted 6 months after the surgery. Results: There was no significant difference in the baseline characteristics and preoperative CT features between the two groups (p > 0.05). The neuroendoscopy group had a lower recurrence rate than the control group (p = 0.043). Besides the neuroendoscopy group had a higher rate of hematoma evacuation (p＜0.001), less pneumocephalus volume (p＜0.001), shorter hospital stay (p＜0.001) and better Markwalder score (p＜0.001) than the control group within 24-48 hours after operation. However, there was no significant difference between the two groups in the incidence of pneumocephalus, Markwalder score (at discharge and 6 months after surgery) and mortality. Moreover, The operation time was longer in the neuroendoscopy group (p＜0.001). Conclusions: When compared with the traditional BHC, rigid neuroendoscopy assisted hematoma resection can better reduce the recurrence rate of CSDH with mixed density. Also, it surpassed the results obtained from BHC in reducing the volume of pneumocephalus, improving hematoma evacuation rate, promoting short-term neurological recovery, and shortening hospital stays.